GSH-responsive poly-resveratrol based nanoparticles for effective drug delivery and reversing multidrug resistance. (31st December 2022) - Liping, Yang; Jian, He; Zhenchao, Tao; Yan, Zhou; Jing, Yang; Yangyang, Zhang; Jing, Gao; Liting, Qian
Abstract: Cancer poses a serious threat to human health and is the most common cause of human death. Polymer-based nanomedicines are presently used to enhance the treatment effectiveness and decrease the systemic toxicity of chemotherapeutic agents. However, the disadvantage of currently polymeric carriers is without therapy procedure. Herein, for the first time, glutathione (GSH)-responsive polymer (PRES) with anti-cancer effect was synthesized following the condensation–polymerization method using resveratrol (RES) and 3, 3′-dithiodipropionic acid. PRES can not only suppress the tumor cells growth but can also self-assemble into nanoparticles (∼93 nm) for delivering antitumor drugs, such as paclitaxel (PTX@PRES NPs). The system could achieve high drug loading (∼7%) and overcome multidrug resistance (MDR). The results from the in vitro studies revealed that the NPs formed of PRES were stable in the systemic circulation, while could be efficiently degraded in tumor cells high GSH environment. Results from cytotoxicity tests confirmed that PTX@PRES NPs could effectively suppress the growth of cancer cells (A549) and drug-resistant cells (A549/PTX). The NPs could also be used to significantly increase the therapeutic efficacy of the drugs in A549/PTX tumor-bearing mice. In vivo investigations also demonstrated that the PRES-based NPs exhibited tumor inhibition effects. In summary, we report that the GSH-responsive polymer synthesized by us exhibited multiple interesting functions and could be used for effective drug delivery. The polymer exhibited good therapeutic effects and could be used to overcome MDR. Thus, the synthesized system can be used to develop a new strategy for treating cancer.